The Power of Scientific Evidence in the Evidence System for Forest and Land Cases - Kusmiharsono, Didik; Sura Anabertha Sembiring, Malemna (Ann Publisher, 2024)
The development of evidence in cases of land and forest fires is regulated in Article 96 of Law Number 32 of 2009 concerning Environmental Protection and Management. In regulating the extent of evidence in environmental cases, the Supreme Court through Decree of the Chief Justice No.36/KMA/SK/II/2013 concerning the Implementation of Guidelines for Handling Environmental Cases. The research in this study is normative juridical legal research or library research. Meanwhile, the literature review uses various secondary data such as primary legal materials. The results of the study show that regulations on the use of scientific evidence (scientific evidence) as evidence in land and forest fire cases are contained in Laws, Ministerial Regulations and Supreme Court Decisions regarding the use of scientific evidence (scientific evidence) as evidence in land fire cases. The obstacle in using scientific evidence (scientific evidence) as evidence in land and forest fire incidents is that the causal relationship element is very difficult to prove so it requires scientific evidence.